2020
DOI: 10.1093/infdis/jiaa656
|View full text |Cite
|
Sign up to set email alerts
|

Independent Side-by-Side Validation and Comparison of 4 Serological Platforms for SARS-CoV-2 Antibody Testing

Abstract: Highly sensitive and specific platforms for the detection of anti-SARS-CoV-2 antibodies are becoming increasingly important for (1) evaluating potential SARS-CoV-2 convalescent plasma donors, (2) studying the spread of SARS-CoV-2 infections and (3) identifying individuals with seroconversion. This study provides a comparative validation of four anti-SARS-CoV-2 platforms. Unique feature of this study is the use of a representative cohort of COVID-19-convalescent patients with mild-to-moderate disease course. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 10 publications
8
69
1
1
Order By: Relevance
“…However, the large sample size, equivalent to ∼10% of the urban population of Qatar, as well as the probabilistic weighting used in the analysis may have reduced inherent biases in our sample. Laboratory methods were based on high-quality, validated commercial platforms, such as the Roche platform used for serological testing [16,31]. The Roche platform is one of the most extensively used and investigated commercial platforms, with a specificity ≥99.8% [16,32,33] and a sensitivity ≥89% [12,31,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the large sample size, equivalent to ∼10% of the urban population of Qatar, as well as the probabilistic weighting used in the analysis may have reduced inherent biases in our sample. Laboratory methods were based on high-quality, validated commercial platforms, such as the Roche platform used for serological testing [16,31]. The Roche platform is one of the most extensively used and investigated commercial platforms, with a specificity ≥99.8% [16,32,33] and a sensitivity ≥89% [12,31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory methods were based on high-quality, validated commercial platforms, such as the Roche platform used for serological testing [16,31]. The Roche platform is one of the most extensively used and investigated commercial platforms, with a specificity ≥99.8% [16,32,33] and a sensitivity ≥89% [12,31,33]. However, it is possible that the less-than-perfect sensitivity, especially for those with recent infections, may have underestimated the actual seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory methods were based on high-quality and validated commercial platforms, such as the Roche platform used for the serological testing [18, 39], one of the best available and extensively used and investigated commercial platforms with a specificity ≥99.8% [18, 40] and a sensitivity ≥95% [7, 39]. However, the less-than-perfect sensitivity may have lowered the measured antibody-positivity prevalence by a few percentage points.…”
Section: Discussionmentioning
confidence: 99%
“…The Roche assay was the weaker predictor of neutralizing capacity (r=0.56, p=0.0001) compared to the Abbott assay (NCP IgG) (r=0.69, p<0.0001), Siemens assay (RDB total antibodies) (r=0.74, p<0.001), and the S1/S2-based DiaSorin assay (S1/S2 IgG ) (r=0.84, p<0.0001) [17]. Jahrsdörfer et al and Padoan et al confirm that the weaker correlation was observed using the Roche assay [11,22], and McAndrews et al found that 86% of individuals positive for RBD-directed antibodies exhibited neutralizing capacity, whereas only 76% of positive NCP-directed antibodies exhibited neutralizing capacity [23]. The fact that anti-NCP assays have the lowest neutralizing capacity could be expected, as neutralizing antibodies are directed to the spike protein responsible for enabling cell entry.…”
Section: To the Editormentioning
confidence: 91%
“…0.128) [9]. The specificity of the test was excellent in several independent evaluations (99.8-100%) [8][9][10][11]. The RT-PCR for SARS-CoV-2 determination in respiratory samples (nasopharyngeal swab samples) was performed on the LightCycler® 480 Instrument II (Roche Diagnostics®) using the LightMix® Modular SARS-CoV E-gene set.…”
Section: To the Editormentioning
confidence: 99%